Faults [videorecording (DVD)] - Stearns, Riley, 1986-; Ellis, Chris, 1956-; Orser, Leland; Winstead, Mary Elizabeth (Screen Media, 2015)
Claire is under the grip of a mysterious new cult called Faults. Desperate to be reunited with their daughter, Claire's parents recruit Ansel, one of the world's foremost experts on mind control to kidnap and deprogram her. However, once the process is underway, Ansel realizes he may not be the one in control.